2018
DOI: 10.1101/472696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating causal associations between previously reported risk factors and epithelial ovarian cancer: a Mendelian randomization analysis

Abstract: Background: Previously reported observational associations between risk factors and epithelial ovarian cancer (EOC) could reflect residual confounding, reverse causation, or measurement error. Mendelian randomization (MR) uses genetic variants as proxies for modifiable risk factors to strengthen causal inference in observational studies. Methods:We used MR to evaluate the causal role of 13 previously reported risk factors in overall and histotype-specific EOC in up to 25,509 case subjects and 40,941 controls i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…28 More than 60 MR studies have been published to date utilizing genetic variants associated with 25OHD to aid causal effect estimation. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] A deeper understanding of the genetic determinants contributing to variation in circulating vitamin D levels could enable an improved instrumentation of vitamin D in MR studies, allow better genomic prediction of vitamin D levels and provide insights into biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…28 More than 60 MR studies have been published to date utilizing genetic variants associated with 25OHD to aid causal effect estimation. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] A deeper understanding of the genetic determinants contributing to variation in circulating vitamin D levels could enable an improved instrumentation of vitamin D in MR studies, allow better genomic prediction of vitamin D levels and provide insights into biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from family history of breast or ovarian cancer, high body mass index in adolescence, diagnosis of endometriosis, and taller height, most established risk factors are hormonal or reproductive [1]. A recent Mendelian randomization (MR) study of 13 known observational risk factors only confirmed genetic liability to lifetime smoking and endometriosis as causal [5]. Thus, identification of additional risk factors is crucial for designing prevention strategies and for earlier diagnosis of EOC.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the MR findings on vitamin D and ovarian cancer did not replicate in subsequent MR analyses [194,326]. I speculate that the reason might be attributable to study design difference and the increasing sample size.…”
Section: Making Sense Of the Pan-cancer Approachmentioning
confidence: 92%